Military justice: the rights of an arrested soldier / Mohamad Bustaman Abdullah - Abdullah, Mohamad Bustaman (Faculty of Law, 1987)
Little is known about the system of military justice which exists in our Armed Forces. To a few, II persons who subjected to service laws (1) II themselves, the system may seem to be familiar. But, to most, admittedly, totally strange. Thus, it is not blameworthy that most civilians are ignorant of the system except for same lawyers and Judge Advocates. Presumably, this is because of the closed nature of the service not usually understood by "persons not subjected to military law ll (2). The lack of knowledge of the system of military justice amongst the Military officers and personnel has resulted in the miscarriage of justice. Ignorant of the system themselves have resulted in them losing their rights available under the law. The law as regard to the Armed Forces may seem to be adequate, however, it could be practical misnormer.